2017
DOI: 10.1002/jso.24669
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of systematic lymph node dissection in advanced epithelial ovarian cancer during interval debulking surgery performed after neoadjuvant chemotherapy

Abstract: Systematic LND may have therapeutic value in advanced EOC patients treated with NAC and IDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 26 publications
(48 reference statements)
0
33
0
Order By: Relevance
“…They showed improvement in OS with a median survival of 28 months for LNS vs. 37 months for LND, with HR = 0.29 (0.15–0.57) p = < 0.001. The same was true with PFS, with HR = 0.637 (0.429–0.946), p = 0.025 [ 28 ]. Concerning PFS, SL had positive impact.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…They showed improvement in OS with a median survival of 28 months for LNS vs. 37 months for LND, with HR = 0.29 (0.15–0.57) p = < 0.001. The same was true with PFS, with HR = 0.637 (0.429–0.946), p = 0.025 [ 28 ]. Concerning PFS, SL had positive impact.…”
Section: Discussionmentioning
confidence: 93%
“…This is the only study evaluating the impact of SL in IDS in patients with advanced serous ovarian adenocarcinoma after NAC. Other studies evaluated the impact of SL in patients with ovarian adenocarcinoma of all histological subtypes after NAC [ 26 , 27 , 28 , 29 , 30 , 31 ]. Our results are consistent with those published [ 26 , 27 , 29 , 30 , 31 ] that did not demonstrate improvement in OS for SL after NAC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this study, extended PAN dissection was not compared directly with conventional PAN dissection. However, the frequency of complications (including pulmonary complications, infection, intestinal complications, thromboembolism, lymphatic complications, and blood transfusion) was similar to or lower than the rates of perioperative complications reported after conventional PAN dissection [8,[11][12][13], suggesting that the safety of extended PAN dissection was not inferior to conventional dissection and that dissecting the supra-renal PANs has little negative impact.…”
Section: Discussionmentioning
confidence: 61%
“…When PDS was performed in patients with T3 cancer, the incidence rate of infra-renal PAN metastasis was reported to be 52-84.7% [6][7][8][9]. In addition, the incidence rate of infra-renal PAN metastasis was reported to be 47.0-78.5% in patients undergoing IDS, suggesting that PAN metastases were still frequent even after NAC [10][11][12]. In the present study, infrarenal PAN metastasis was observed in 1 out of 14 patients with T1 and T2 cancer (7.1%) versus 8 out of 11 patients with T3 cancer (72.7%).…”
Section: Discussionmentioning
confidence: 99%